El deber de gestión del riesgo de corrupción en la empresa emanado de la ley 20393 de Chile: especial referencia a las exigencias de identificación y evaluación de riesgo - Artaza, Osvaldo (2018)
This article analyzes the criteria to determine when a company has failed to meet it is duty to manage the risks of bribery that arise over the course of it is economic activity. Special emphasis has been placed on the establishment of requirements for identifying such risks with the purpose of being able to adopt measures to counteract them later. The article analyzes comparative experience, both in relation to the technical guidelines that come from compliance studies, as well as the studies of criminology of corporate crime. Those experiences are explored to identify a series of structural and cultural variables that would predict the commission of crimes and, therefore, require their identification by the company.